Quality of life in patients with oculocutaneous albinism - Maia, Marcus; Volpini, Beatrice Mussio Fornazier; Santos, Gabriela Alves dos; Rujula, Maria Josefa Penon (Anais brasileiros de dermatología, 2015)
The social reality of the albino needs to be more studied in Brazil, as myths and social segregation regarding this illness are likely to be found in the country, with psychosocial and medical implications. As this subject has not been referenced in previous scientific articles in Brazil, this research intends to evaluate the quality of life of the albinos that treated at our medical institution. The quality of life was evaluated through the WHOQOL-BREF. Furthermore, two aspects of main relevance in the lives of the albinos were also objects of research, low vision and skin cancer. The sample consisted of forty oculocutaneous albinos and a control group of forty healthy individuals, matched by sex and age. Among the participants, 57.7% were between 18 and 40 years old, 28.2% were between 41 and 60, and 14.1% were over 60. 42.1% had skin cancer before the study, 18.4% had skin cancer during the study and 89.5% stated visual deficit. The results obtained in the questionnaires showed a statistically significant difference in the physical domain, with P < 0.001. Low vision combined with skin lesions and social stigma may contribute to disturbances in the quality of life of oculocutaneous albinos. The results presented in this study demonstrated the vulnerability of the affected individuals and the special care required by those patients, at the same time that the need for further research is highlighted in order to better elucidate the aspects related to albinism.